2006
DOI: 10.1007/s00726-005-0292-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal changes of plasma acute phase proteins in schizophrenia and the relation between schizophrenia and haptoglobin (Hp) gene

Abstract: In this study we focused on detecting schizophrenia related changes of plasma proteins using proteomic technology and examining the relation between schizophrenia and haptoglobin (Hp) genotype. We investigated plasma proteins from schizophrenic subjects (n = 42) and healthy controls (n = 46) by two-dimensional gel electrophoresis (2-DE) in combination with mass spectrometry. To further reveal the genetic relationship between acute phase proteins (APPs) and schizophrenia disease, we tested Hp alpha1/Hp alpha2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 43 publications
5
54
0
1
Order By: Relevance
“…In a study focused on detecting schizophrenia-related changes of plasma proteins, Wan et al (169) used proteomic technology to examine the relation between schizophrenia and HP genotype. The authors investigated plasma proteins from schizophrenic subjects and healthy controls by two-dimensional gel electrophoresis in combination with mass spectrometry.…”
Section: Diseases Of the Nervous Systemmentioning
confidence: 99%
“…In a study focused on detecting schizophrenia-related changes of plasma proteins, Wan et al (169) used proteomic technology to examine the relation between schizophrenia and HP genotype. The authors investigated plasma proteins from schizophrenic subjects and healthy controls by two-dimensional gel electrophoresis in combination with mass spectrometry.…”
Section: Diseases Of the Nervous Systemmentioning
confidence: 99%
“…Wan, et al reported that the expression of serum amyloid P-component was significantly higher in the plasma of patients with schizophrenia in comparison with that of healthy controls [22]. Alterations in immune response may be an important component in the etiopathogenesis of schizophrenia.…”
Section: Serum Proteome Analysis Of Catatoniamentioning
confidence: 99%
“…It means that retinol binding protein has negative effects in transferring vitamin A from maternal liver storage sites to the placenta and is relation to avoid MAC disease [29]. In 2006, Wan, et al determined the levels of retinol binding protein, no statistical difference was found at gene expression level of schizophrenic patients in comparison with that of healthy controls [22]. Chen and his colleagues (2011) observed schizophrenic patients with metabolic syndrome in higher RBP4 and lower total adiponectin and high molecular weight adiponectin levels.…”
Section: Serum Proteome Analysis Of Catatoniamentioning
confidence: 99%
“…An upregulation of APP genes has been found in schizophrenia, especially in the prefrontal cortex, and that that these genes overlap in the schizophrenia susceptibility loci. It has been suggested that acute phase reaction may be an aetiological agent in the pathophysiology of schizophrenia, but not just an accompanying symptom (186)(187)(188).…”
Section: The Immunological Markersmentioning
confidence: 99%